A REVIEW ON MICROPLASTIC IN THE SOILS AND THEIR IMPACT ON SOIL MICROBES, CROPS AND HUMANS - Bansal, O.P.; Singh, Anjul (International Journal of Research -GRANTHAALAYAH, 2022)
For modern human life, since the beginning of the 21st century, plastic become indispensable. The golden period for the plastic industry was the second half of the 20th century when plastic-based products bucket to the car were manufactured. Due to mismanagement, and indiscriminate use microplastics are emerging as persistent terrestrial pollutants. In the last decade, environmental scientists and other stakeholders have paid serious attention to soil pollution by microplastics. In soils, the microplastic particles act as a vector for the toxic persistent organic pollutants and potentially toxic metals which are easily sorbed by plants and enter the food chain. Microplastic pollutants not only influence the soil’s physicochemical properties but also impact the feeding habits of soil biota. Microplastic in soils is due to sewage sludge, bio waste compost amendments, plastic mulching, wastewater irrigation, leachate from landfills and atmospheric deposition. The quantity of microplastic particles in the soils varied from nil to13000 items per kg of soil. The quantity of microplastic in the soil is 5-23 times that in the ocean. The microplastic in soil retards seed germination and plant growth. Enzymatic activities of the soil are also influenced by microplastic. Plastic Pellets, Personal Care Products and Cosmetics, Synthetic Textiles, the Abrasion of Tyres, City Dust, and the Abrasion of Road Markings etc. are the environmental sources of microplastic. Intake by humans via food causes respiratory toxicity, cytotoxicity, immunotoxicity and reproductive toxicity among other effects. The present work reports the sources and distribution of microplastic in the soil environment and their impact on soil biota, plants, and human health.